Involvement of oxidative stress in municipal landfill leachate-induced toxicity in boar sperm (2013)
Exposure to leachates generated from an improperly managed hazardous waste dump sites is detrimental to human health and the ecosystem. The present study investigated the effect of Olushosun municipal landfill leachate (OMLL) on sperm characteristics and antioxidant systems in boar sperm cells. The sperm cells were incubated with the leachate at final concentrations of 0, 1, 2, 4 and 8% for 3 h at 37◦C. Sperm characteristics were monitored hourly during the incubation period whereas amino transferases activities and oxidative stress indices were determined after the incubation period. Results revealed a time- and dose-dependent decline in sperm progressive motility from 1 h post-treatment with 2, 4 and 8% OMLL whereas decreased sperm viability with elevated abnormalities were observed from2 h post-treatment with 4 and 8% OMLL when compared with control. Exposure to OMLL caused a significant increase in aminotransferases, catalase and glutathione-S-transferase activities whereas it markedly decreased superoxide dismutase and glutathione peroxidase activities without affecting glutathione level in the treated sperm cells. Co-incubation of sperm with OMLL increased the levels of hydrogen peroxide and malondialdehyde levels. In conclusion, OMLL elicited spermatotoxicity via induction of oxidative stress possibly generated through an enhanced intracellular reactive oxygen species.